MHealth resources for asthma and pregnancy care: Methodological issues and social media recruitment. A discussion paper. (17th July 2018) - Williamson, Graham R.; O'Connor, Anita; Chamberlain, Chervonne; Halpin, David
Abstract: Aims: A discussion of methodological issues and social media recruitment to a feasibility study to investigate mHealth resources for asthma and pregnancy care. Background: Pregnant women with asthma are reported to be poorly supported according to an international research. We sought to establish if a mHealth intervention might be feasible and acceptable to them. Design: A Phase I or modelling study. Methods: A project team designed an intervention to address UK national guidelines for the management of asthma during pregnancy, using other resources already accessible on the web. This was made available on a project website optimized for mobile phone usage. Links were Tweeted and advertised on Facebook, asking participants to access the project website, which included links to the resources and before‐ and after‐use questionnaires to establish baseline symptom data and participant views of the resources. Results: Despite 55, 700 Twitter impressions in a 76‐day period over winter 2016–2017, this recruitment strategy garnered 402 engagements but only seven respondents for questionnaire 1 and zero respondents for questionnaire 2. Conclusions: We could not recruit to this study despite believing that social media recruitment would be effective and we recommend that social media recruitment be used cautiously. Apparently, we did not sufficiently address the theoretical aspects of communications theory and were not clear enough about our key messages. Publication bias may exist about the non‐publication of other failed telemedicine studies using social media; this goes largely unreported in some systematic reviews and may influence researchers' decision‐making about social media recruitment. Abstract : 摘要: 目的: 旨在探讨可行性研究中方法论问题和社交媒体招募情况, 以对用于护理患有哮喘的孕妇的移动医疗资源进行调查。 背景: 据国际研究报道, 患有哮喘的孕妇获得的支持不足。我们试图确定移动医疗资源干预措施是否对哮喘孕妇可行且可为她们所接受。 设计: 第一阶段或建模研究。 方法: 项目团队设计了一项干预措施, 利用网上已有的其他资源, 制定了对英国妊娠期哮喘患者进行管理的国家指南。该国家指南可以在针对手机使用而优化的项目网站查阅到。链接网站为推特, 发布广告的网站是脸书, 要求参与者访问项目网站, 其中包括资源链接以及使用前和使用后的调查问卷, 以创建基线症状数据和参与者对资源的看法。 结果: 尽管在2016年至2017年冬季的76天内有55700人次访问推特, 且招募策略使得402人次参与本项目, 但是提交1号调查问卷的受访者只有7位, 而提交2号调查问卷的受访者则是0位。 结论: 尽管我们认为社交媒体招募措施会有效, 但我们仍然不能为这项研究招募到参与者, 我们建议需谨慎使用社交媒体进行招募。显然, 我们没有彻底解决通信理论的理论方面的问题, 也没有清楚的表达我们的关键信息。关于使用社交媒体未能发表其他失败的远程医疗研究的问题, 其中可能存在发表偏倚;这在一些系统评价中基本没有报道, 可能会影响研究人员关于社交媒体招募作出的决策。